Prevalence of blindness and its determinants in Bangladeshi adult population: results from a national cross-sectional survey. Issue 4 (1st April 2022) - Shakoor, Shawkat Ara; Rahman, Mustafizur; Hossain, A H M Enayet; Moniruzzaman, Mohammad; Bhuiyan, Mahfuzur Rahman; Hakim, Ferdous; Zaman, M Mostafa
Abstract : Objective: The objective of this study was to determine the prevalence of blindness and its determinants in Bangladeshi adult population. Study design: A cross-sectional population-based survey conducted at household level with national representation. Samples were drawn from the 2011 national census frame using a multistage stratified cluster sampling method. Setting and participants: The survey was done in urban and rural areas in 2013 using a probability proportionate to size sampling approach to locate participants from 72 primary sampling units. One man or one woman aged ≥40 years was randomly selected from their households to recruit 7200. In addition to sociodemographic data, information on medication for hypertension and diabetes was obtained. Blood pressure and capillary blood glucose were measured. Eyelids, cornea, lens, and retina were examined in addition to visual acuity and refraction testing. Primary outcome measures: The following definition was used to categorise subjects having (1) blindness: visual acuity <3/60, (2) low vision: ≥3/60 to <6/60 and (3) normal vision: ≥6/12 after best correction. Results: We could recruit 6391 (88.8%) people among whom 2955 (46.2%) were men. Among them, 1922 (30.1%) were from urban and 4469 (69.9%) were from rural areas. The mean age was 54.3 (SD 11.2) years. The age-standardised prevalence, after best correction, of blindness and low vision was 1.0% (95% CI 0.5% to 1.4%) and 12.1% (95% CI 10.5% to 13.8%), respectively. Multivariable logistic regression indicated that cataract, age-related macular degeneration and diabetic retinopathy were significantly associated with low vision and blindness after adjustment for age and sex. Population attributable risk of cataract for low vision and blindness was 79.6%. Conclusions: Low vision and blindness are common problems in those aged 40 years or older. Extensive screening and eye care services are necessary for wider coverage engaging all tiers of the healthcare system especially focusing on cataract.